In Vitro Assessment of SWEEPS and Antimicrobial Photodynamic Therapy Alone or in Combination for Eradicating Enterococcus faecalis Biofilm in Root Canals - Ali Shahi Ardakani; Shima Afrasiabi; Pegah Sarraf; Stefano Benedicenti; Luca Solimei; Nasim Chiniforush (MDPI AG, 2023)
Objectives: This study investigates the efficacy of antimicrobial photodynamic therapy (aPDT) using riboflavin and a blue diode laser (BDL), combined with shock wave-enhanced emission photoacoustic streaming (SWEEPS), against Enterococcus faecalis. Materials and Methods: A total of 48 extracted single-rooted human teeth were used. The root canals were instrumented, sealed at their apices, had the smear layer removed, and then underwent autoclave sterilization. Subsequently, each canal was inoculated with E. faecalis bacterial suspension and allowed to incubate for ten days. After confirming the presence of biofilms through scanning electron microscopy (SEM) in three teeth, the remaining teeth were randomly allocated into nine groups, each containing five teeth: control, 5.25% sodium hypochlorite (NaOCl), BDL, SWEEPS + normal saline, SWEEPS + NaOCl, riboflavin, riboflavin + SWEEPS, riboflavin + BDL, and riboflavin + BDL + SWEEPS. After the treatment, the numbers of colony-forming units (CFUs)/mL were calculated. The data were analysed using one-way ANOVA followed by Tukey's test for comparisons. Results: All groups, with the exception of the BDL group, exhibited a significant reduction in E. faecalis CFU/mL when compared to the control group (p < 0.001). The difference in CFU/mL value between riboflavin + BDL + SWEEPS and riboflavin + SWEEPS was significant (p = 0.029), whereas there was no significant difference between riboflavin + BDL + SWEEPS and riboflavin + BDL (p = 0.397). Moreover, there was no statistically significant difference between the riboflavin + SWEEPS group and the riboflavin + BDL group (p = 0.893). Conclusions: The results demonstrated that combining the SWEEPS technique with riboflavin as a photosensitizer activated by BDL in aPDT effectively reduced the presence of E. faecalis in root canals.